Soof - Weeks, Sarah 1955- (Scholastic Press, 2018)
All her life Aurora has heard stories about how wonderful and lucky Heidi is, and soon this paragon (now grown up and expecting a baby) will be visiting; but before she arrives part of their house is damaged in a fire, and worse, Aurora's beloved dog disappears...and while her parents have always believed in "soof" (Heidi's mom's word for love), Aurora, who has never really fit in with children her own age, will just have to find her own soof